TELAAH TERHADAP AKTIVITAS PERTAMBANGAN YANG BERDAMPAK PADA LINGKUNGAN HIDUP DI INDONESIA DILIHAT DARI SUDUT PANDANG ANALYSIS ECONOMIC OF LAW - Kurniasih, Ida (The Juris, 2023)
The Indonesian government believes that the structure and modus operandi of the domestic and international mining industry has changed dramatically and that it is necessary to address the changes. Correspondingly, mining activities will always have tensions that have local and global impacts, especially related to the environment. So this research seeks to examine the availability of regulations on mining activities that have an impact on the environment in Indonesia by using economic analysis of law. This research is a normative legal research. The results found that using the principles of economic analysis of law to study the regulation and management of mining activities can achieve a balance between environmental protection and economic efficiency. Some principles that can be used in this analysis include: a) use of economic instruments; b) cost-benefit analysis; c) imposition of sanctions and incentives; d) evaluation of risks and impacts; and e) involving related parties. In this context, mining legal norms are one of the sectoral laws in the field of environment that are used to integrate environmental protection in an effort to achieve sustainable and environmentally sound mining governance, with the aim of supporting the sustainability of human life and living things.